Biophysical Measurements and Ultrasonographic Findings in Chronic Dermatitis in Comparison with Uninvolved Skin - Yazdanparast, Taraneh (Indian J Dermatol, 2019)
BACKGROUND: Nowadays noninvasive techniques are performed to evaluate the biophysical properties of skin in vivo. AIMS: The aim of this study was to evaluate the biophysical and ultrasonographic properties of skin in chronic contact or atopic dermatitis to provide better insight into pathogenesis, diagnosis, and treatment response. MATERIALS AND METHODS: The stratum corneum hydration, transepidermal water loss (TEWL), pH, erythema, melanin, sebum, friction, temperature, elasticity parameters (R0, R2, and R5), the thickness and echo-density of epidermis, dermis, and subepidermal low-echogenic band (SLEB) were measured on lesional, perilesional, and symmetrical skin of 22 chronic dermatitis patients. The average of perilesional and symmetrical skin values (control) was compared with lesional values. RESULTS: Stratum corneum hydration (P<0.001), friction (P=0.02), sebum (P=0.01), and R0 (P<0.001) were significantly lower in lesion, TEWL (P=0.03), pH (P=0.001), erythema (P=0.004), and temperature (P=0.04) were significantly higher in lesion. The thickness of epidermis (P=0.002), dermis (P=0.034), and SLEB (P<0.001) were significantly higher in lesion; and the echo-density of dermis (P<0.001) and SLEB (P<0.001) was significantly lower in lesion. CONCLUSION: Chronic contact and atopic dermatitis are characterized by certain changes in biophysical and biomechanical properties of the skin. The evaluation of these parameters might be useful in the early diagnosis and assessment of treatment response.